Penerapan Pembiasaan Tri Hita Karana untuk Meningkatkan Pendidikan Karakter Gotong Royong Siswa SD - Ni Putu Ayu Emalasari; I Gusti Agung Ayu Wulandari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
There are still many students who do not carry out pickets in the classroom together. The students have not yet understood the meaning of the character value of mutual aid. The purpose of this study is to be able to improve the character of mutual cooperation through the habituation of Tri Hita Karana. This research is a class action research. The subjects in this study were class V students totaling 20 people. This research was carried out using 2 cycles, each of which cycle consists of four stages, namely: (1) Action Planning, (2) Action Implementation (3) Observation (4) Reflection. In this study, a data collection method was used, namely the non-test method. And for theexample of data collection in this study is observation and documentation techniques. As for the data analysis techniques used in this study, they are qualitative and quantitative analysis techniques. In this study, researchers used several aspects of measuring the character of mutual cooperation based on Tri Hita Kirana, namely the concept of pawongan which was then described through several indicators. The results of the implementation of the actions of cycle I and the implementation of cycle II obtained the average score of student character results in cycle I, which was 70% which was in the good category and the average score of student character results in cycle II was 85% which was in the very good category. Based on this, it can be concluded that through the habituation of Tri Hita Karana, the character ofmutual aid can increase and become a habit if given repeated treatment and action.